Skill based syllabus design: Learning a foreign language in adult learners. - Sarmiento González, Lady Paola; Gamboa González, Ángela María; Asesor (Corporación Universitaria Minuto de Dios, 2016)
The following research project is qualitative case study which emerged after my experience as a tutor for the English course for adult learners at Uniminuto. Taking into account the students‟ needs and interests a skill-based syllabus was designed as a proposal that aimed to suggest the reopening of the basic English course with the intention to be implemented and developed in the future in order to provide learning environments where adult learners may improve the four skills of the language (reading – writing – listening - speaking) through social awareness topics that engage people to be conscious about the social role that each person plays in a community. In addition, this skill-based syllabus can be taken as a proposal providing the course for adult people with a better organization that might allow participants to learn English as a foreign language.
Keywords: Foreign Language; Skill-Based Syllabi; English Course for Adults; Syllabus Design; Ingles-Enseñanza; Lenguas Modernas-Enseñanza; Enseñanza Bilingüe; Escuela de Idiomas